Avoidance of tobacco health warnings? An eye‐tracking approach. (2nd July 2020) - Sillero‐Rejon, Carlos; Leonards, Ute; Munafò, Marcus R.; Hedge, Craig; Hoek, Janet; Toll, Benjamin; Gove, Harry; Willis, Isabel; Barry, Rose; Robinson, Abi; Maynard, Olivia M.
Abstract: Aims: Among three eye‐tracking studies, we examined how cigarette pack features affected visual attention and self‐reported avoidance of and reactance to warnings. Design: Study 1: smoking status × warning immediacy (short‐term versus long‐term health consequences) × warning location (top versus bottom of pack). Study 2: smoking status × warning framing (gain‐framed versus loss‐framed) × warning format (text‐only versus pictorial). Study 3: smoking status × warning severity (highly severe versus moderately severe consequences of smoking). Setting: University of Bristol, UK, eye‐tracking laboratory. Participants: Study 1: non‐smokers ( n  = 25), weekly smokers ( n  = 25) and daily smokers ( n  = 25). Study 2: non‐smokers ( n  = 37), smokers contemplating quitting ( n  = 37) and smokers not contemplating quitting ( n  = 43). Study 3: non‐smokers ( n  = 27), weekly smokers ( n  = 26) and daily smokers ( n  = 26). Measurements: For all studies: visual attention, measured as the ratio of the number of fixations to the warning versus the branding, self‐reported predicted avoidance of and reactance to warnings and for study 3, effect of warning on quitting motivation. Findings: Study 1: greater self‐reported avoidance [mean difference (MD) = 1.14; 95% confidence interval (CI) = 0.94, 1.35, P  < 0.001, ηp 2  = 0.64] and visual attention (MD = 0.89, 95% CI = 0.09, 1.68, P  = 0.03, ηp 2  = 0.06) to long‐term warnings, but not for reactance (MD = 0.14, 95% CI = –0.04, 0.32, P  = 0.12, ηp 2  = 0.03). Increased visual attention to warnings on the upper versus lower half of the pack (MD = 1.8; 95% CI = 0.33, 3.26, P  = 0.02, ηp 2  = 0.08). Study 2: higher self‐reported avoidance of (MD = 0.70; 95% CI = 0.59, 0.80, P  < 0.001, ηp 2  = 0.61) and reactance to (MD = 0.37; 95% CI = 0.27, 0.47, P  < 0.001, ηp 2  = 0.34) loss‐framed warnings but little evidence of a difference for visual attention (MD = 0.52; 95% CI = –0.54, 1.58, P  = 0.30, ηp 2  = 0.01). Greater visual attention, avoidance and reactance to pictorial versus text‐only warnings (all P s < 0.001, ηp 2  > 0.25). Study 3: greater self‐reported avoidance of (MD = 0.37; 95% CI = 0.25, 0.48, P  < 0.001, ηp 2  = 0.33) and reactance to (MD = 0.14; 95% CI = 0.05, 0.23, P  = 0.003, ηp 2  = 0.11) highly severe warnings but findings were inconclusive as to whether there was a difference in visual attention (MD = –0.55; 95% CI = –1.5, 0.41, P  = 0.24, ηp 2  = 0.02). Conclusions: Subjective and objective (eye‐tracking) measures of avoidance of health warnings on cigarette packs produce different results, suggesting these measure different constructs. Visual avoidance of warnings indicates low‐level disengagement with warnings, while self‐reported predicted avoidance reflects higher‐level engagement with warnings.